Appréciation de l’infestation de la mouche de l’olive Bactrocera oleae Gmelin, 1788 (Diptera, Tephritidae) dans un verger oléicole dans la région d’Ouanougha, wilaya de M’sila - ALILICHE, Khadidja. CHIKHI, Nadjet (Université Mohamed BOUDIAF de M'Sila, 2019)
The olive tree is one of the most characteristic trees in the Mediterranean region. It has a great importance on the stands of this region. The olive tree is exposed to many pests including the olive fly Bactrocera oleae. The study orchard of El Makmane (Ouanougha) is heavily infested by the fly which causes considerable losses in pulp and losses due to the fall. During the autumn period females of the fly prefer olives of medium diameter to deposit their eggs. The exit towers left by the fly on the olives are points of entry for the parasites which has repercussions on the quality of the oil.
Keywords: olive tree, Bactrocera oleae, infestaion, loss and Ouanougha